The variability of stemflow generation in a natural beech stand (Fagus orientalis Lipsky) in relation to rainfall and tree traits. Issue 3 (17th February 2020) - Dezhban, Atefeh; Attarod, Pedram; Zahedi Amiri, Ghavamudin; Pypker, Thomas G.; Nanko, Kazuki
Abstract: Stemflow (SF) has been recognised as an important process that can exert considerable effects on the hydrology, biogeochemistry, and ecology of wooded ecosystems. The aim of this study was to quantify the relationship between SF (yields and funnelling ratios, FRs) of beech ( Fagus orientalis ) trees and rainfall characteristics, to evaluate the effects of tree traits on SF yield and the magnitudes of FRs in differing rainfall classes. Event‐based measurements were carried out from April 2016 to November 2017 during the leafed‐out periods in a natural uneven‐aged beech stand located in the Hyrcanian forest of Iran. Tree density in the studied plot was 188 trees ha −1 with a basal area of 51 m 2 ha −1 . SF volume was measured in three diameter classes (10–40, 40–70, and >70 cm; n = 3 per class). During the 25 rainfall events SF, SF%, and FR were 3.22 mm, 0.41%, and 1.11 on average, respectively. The linear regression analysis revealed that gross rainfall had the strongest correlation with SF yield and FR ( P value <.01). The linear regression with the trees structural traits indicated that canopy projected area, diameter at breast height (DBH), and mosses cover percentage, respectively, strongly influence SF yield for rainfall <15 to >50 mm. FR significantly decreased with increasing tree height, DBH, and mosses cover percentage (all P values <.05). Smaller trees concentrated more SF than tall and large DBH trees. Pearson correlation analysis indicated tree height, canopy projected area, and MCP were positively and significantly correlated to DBH ( P value <.01; r ≥ .87). Therefore, SF generation in the present study is more associated with DBH. Our findings could assist managers to optimise the management strategies of deciduous forest via promotion of some large DBH trees along with small DBH trees to optimise water inputs via SF in water‐limited forest ecosystems.